2003
DOI: 10.1152/ajpendo.00508.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles and protein balance in skeletal muscle of burned children after β-adrenergic blockade

Abstract: Propranolol, a nonselective β-blocker, has been shown effective in hypermetabolic burn patients by decreasing cardiac work, protein catabolism, and lipolysis. This study investigates the effect of propranolol on gene and protein expression changes in skeletal muscle of burned children by use of high-density oligonucleotide arrays to establish the genetic profiles and stable isotope technique to quantitate protein synthesis. Thirty-seven children (mean age 9.7 ± 1.1 yr) were randomized into groups to receive pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 46 publications
5
22
0
Order By: Relevance
“…Recent advances in adjunctive treatments, such as the use of beta blockers and oxandrolone, were less likely to be applied to patients during the study period than in the present. Beta blockers attenuate hypermetabolic states in children with burn injuries (16), and limited evidence from an adult sample suggests that they may potentially improve outcomes, including mortality (17). Although the effect of oxandrolone treatment on mortality has not been investigated, the use of oxandrolone with severely burned children has been shown to improve muscle protein metabolism, lean body mass, and bone mineral content and to reduce acute phase protein levels (18Y 21).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in adjunctive treatments, such as the use of beta blockers and oxandrolone, were less likely to be applied to patients during the study period than in the present. Beta blockers attenuate hypermetabolic states in children with burn injuries (16), and limited evidence from an adult sample suggests that they may potentially improve outcomes, including mortality (17). Although the effect of oxandrolone treatment on mortality has not been investigated, the use of oxandrolone with severely burned children has been shown to improve muscle protein metabolism, lean body mass, and bone mineral content and to reduce acute phase protein levels (18Y 21).…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent study afforded by participation in a large multisite study 9 allowed identification of six genes up-regulated and two genes down-regulated with the administration of propranolol to burned children, suggesting the eventual possibility of targeting our interventions with greater specificity. 10 Burn injury also results in severe deconditoning and fatigue that can significantly impact functional aptitude. A 3-year outcome study at Harborview Medical Center in Seattle, Washington, revealed an almost-universal complaint of fatigue as a major barrier to return to work and other daily activities.…”
Section: What Is Known About Restoration Of Functionmentioning
confidence: 99%
“…To date most ␤-blockers are administered as the racemic mixture, although only the S-enantiomer is active at the receptor. The mechanism of action of ␤-blockers has been studied at the gene expression level (14). However, little is known about their action at the protein level.…”
mentioning
confidence: 99%